The impact of IFRS on industry - Lavi, Mohan R. (Hoboken : Wiley, 2016)
'The industry-specific guide to IFRS interpretation and application One of the biggest challenges of any reporting standard is how best to interpret and implement it in the context of a specific company or industry, given that each industry has its own intricacies and nuances. The Impact of IFRS on Industry provides specific guidance on applying IFRS in a diverse range of sectors. Opening with an overview of IFRS, including a summary of all the standards, the book goes on to provide detailed coverage of the standards that can impact all industries, including IAS-40, IFRS 1, and IFRS 5. Thereafter, it offers practical advice and guidance on the application of IFRS in specific industries, including automotive; oil and gas; bio-sciences; infrastructure; airlines; media and communications; government-owned entities; mining; software; banking and financial services; insurance; FMCG; shipping; pharmaceuticals; telecoms; real estate and construction; power; SMEs; retail; e-commerce; and the service sector. The book concludes with a discussion on the collateral impact of implementing IFRS and how forthcoming IFRS Standards could impact specific industries. Worked examples are used throughout to demonstrate how the standards are applied in practice. Understand the IFRS standards comprehensively Learn which standards impact all industries Examine the ways in which IFRS is applied in practice See how different standards are applied in specific industries Suitable as a quick reference or a comprehensive guide, The Impact of IFRS on Industry gives you the real-world IFRS answers you need'--
Includes index.
Description based on print version record and CIP data provided by publisher.
Includes bibliographical references and index.
Keywords: Financial statements -- Standards -- Handbooks, manuals, etc; Accounting -- Standards -- Handbooks, manuals, etc; Electronic books